2018
DOI: 10.28942/ejcs.v1i4.36
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Disease and Maternal Diabetes Mellitus

Abstract: Diabetes mellitus is a relatively common illness that can complicate pregnancy and result in an increased incidence of congenital malformations. Offspring of diabetic mothers suffering from type IDDM have a fivefold incidence of congenital malformations compared to pregnancies in the general healthy population. Specifically, the pattern of congenital heart disease (CHD) encountered among this group, with an emphasis on abnormalities of laterality, looping and conotruncal septation, suggesting that the maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…In contrast to that, our OR (1.88) was within a narrow confidence interval (CI: 1.1-3.22). Petropoulos et al 30 concluded that the evidence sufficiently supports declaring pregnancies in mothers with gestational diabetes to have a similar risk to insulin-dependent diabetes mellitus in developing CHD, and to include them among the high-risk group needing fetal cardiac consultation. A possible cofounder that was overlooked is the association between pre-pregnancy BMI and the risk of CHD in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to that, our OR (1.88) was within a narrow confidence interval (CI: 1.1-3.22). Petropoulos et al 30 concluded that the evidence sufficiently supports declaring pregnancies in mothers with gestational diabetes to have a similar risk to insulin-dependent diabetes mellitus in developing CHD, and to include them among the high-risk group needing fetal cardiac consultation. A possible cofounder that was overlooked is the association between pre-pregnancy BMI and the risk of CHD in offspring.…”
Section: Discussionmentioning
confidence: 99%